2009
DOI: 10.1359/jbmr.081104
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Dickkopf-1 (Dkk1) Removes Suppression of Bone Formation and Prevents the Development of Osteolytic Bone Disease in Multiple Myeloma

Abstract: Multiple myeloma (MM) is associated with the development of osteolytic bone disease, mediated by increased osteoclastic bone resorption and impaired osteoblastic bone formation. Dickkopf-1 (Dkk1), a soluble inhibitor of wingless/int (Wnt) signaling and osteoblastogenesis, is elevated in patients with MM and correlates with osteolytic bone disease. In this study, we investigated the effect of inhibiting Dkk1 on the development of osteolytic lesions in the 5T2MM murine model of myeloma. We showed that Dkk1 is ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
168
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(176 citation statements)
references
References 49 publications
5
168
0
3
Order By: Relevance
“…Since TNF-a seemed to increase the levels of other canonical Wnt proteins, we investigated the activation of the canonical Wnt signaling pathway with anti-Dkk1 antibodies. Stimulatory effects of anti-Dkk1 antibodies have recently been reported in mouse primary osteoblasts [17], and are consistent with the beneficial effects of anti-Dkk1 antibodies on bone formation in vivo [10,17,35,36]. In our experiments, blocking Dkk1 slightly increased TNAP expression in osteoblasts differentiating from human MSCs.…”
Section: Discussionsupporting
confidence: 91%
“…Since TNF-a seemed to increase the levels of other canonical Wnt proteins, we investigated the activation of the canonical Wnt signaling pathway with anti-Dkk1 antibodies. Stimulatory effects of anti-Dkk1 antibodies have recently been reported in mouse primary osteoblasts [17], and are consistent with the beneficial effects of anti-Dkk1 antibodies on bone formation in vivo [10,17,35,36]. In our experiments, blocking Dkk1 slightly increased TNAP expression in osteoblasts differentiating from human MSCs.…”
Section: Discussionsupporting
confidence: 91%
“…In vivo studies using both murine and humanized models of MM-bone disease confirmed the bone-anabolic properties of DKK1 antagonists, with increased bone formation, increased OB number and improvement of osteolytic lesions [31,33,34]. Importantly, two studies showed a significant reduction in tumor burden, mainly as an indirect effect via modification of the tumor microenvironment by DKK1 inhibition [31,33].…”
Section: Treatment Of MM Bone Disease With Bone-anabolic Agentsmentioning
confidence: 71%
“…Neutralizing antibodies against DKK1 promote OB differentiation [30] and limit MM cell proliferation when co-cultured with BMSC [33]. In several in-vivo models of MM bone disease, DKK1 inhibition prevents tumor-induced bone destruction, increases trabecular bone formation in both bones bearing MM cells and uninvolved bones, and reduces tumor burden [31,33,34].…”
Section: Pathogenesis Of Osteoblast Inhibition In MMmentioning
confidence: 99%
“…25 Similarly, enhancing marrow stromal cell differentiation into osteoblasts decreases tumor growth and bone destruction, as well as increases bone formation. 26,27 Unfortunately, myeloma is still incurable for most patients and MMBD remains a major contributor to the morbidity and mortality of myeloma patients.…”
Section: Mechanisms Of Mmbdmentioning
confidence: 99%